Influence of playing position and competitive periods on training load indicators in professional soccer - Freitas, V. G. G.; Steinmetz Coelho, M.; Nkenge-Hinds, I.; Uchida, M. C.; Aquino, R. (Serbian Journal of Sports Sciences, 2021)
This study aimed to compare the external and internal training load indicators according to playing positions and competitive periods during a season with professional Brazilian soccer players. Twenty-three professional soccer players were divided by playing positions and monitored over 16 weeks. Internal training load (ITL) was obtained using Rating of Perceived Exertion (RPE), Session Rating of Perceived Exertion (sRPE), Perceived Recovery Scale (PRS), and Delayed Onset Muscle Soreness Scale (DOMS). The external load (ETL) was registered using Global Positioning System (GPS Polar Team Pro 10 Hz), including the total distance covered (TD) and distance in different speed zones (High Speed Running - HSR; >16 km·h-1). Results displayed that season periods influenced PRS, DOMS, ITL and ETL for all playing positions. The competitive period showed higher values of PRS for Forwards (PSR: p < 0.001) and Midfielders (PSR: p < 0.001) and DOMS for Central Defenders (p < 0.001), Full Backs (p = 0.01), Midfielders (p < 0.001) and Forwards (p < 0.001). ITL and ETL were dissimilar only for Midfielders with higher values during competitive periods (sRPE: p = 0.001; TD: p = 0.018; HSR: p = 0.002). PRS and DOMS was influenced by the season`s period based on playing positions, while ETL and ITL were disparate only for Midfielders. The 16 microcycles showed homogeneity concerning perceived recovery and DOMS, with non-linear ITL and ETL characteristics throughout the weeks.